IMPACT OF NEWCASTLE DISEASE ON THE LIVELIHOOD OF SMALLHOLDER INDIGENOUS CHICKEN FARMERS IN SELECTED NORTHERN STATES, NIGERIA - Gukut, M. Y.; Abdullahi, S.; Murtala, N.; Chabiri, L. A.; Ifende, V. I.; Weka, R.; Haruna, I. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study assessed the impact of Newcastle disease (ND) on the livelihoods of smallholder indigenous chicken farmers in Bauchi, Plateau, and Kano States, using both descriptive and inferential statistics. A multistage sampling technique was used to select 810 respondents from the study area. Data were collected through the administration of structured questionnaires and focus group discussions (FGD) and analysed using descriptive statistics and propensity score matching (PSM). The results revealed that the majority of farmers (72.6%) were female, 67.2% were married, middle-aged (mean = 38.5 years), with a modest mean flock size (16 birds), and an average income of ₦108,916. Education levels were varied, with many farmers having qur’anic or primary education. Most farmers kept chickens for cultural ceremonies (78.3%), medical bill payments (70%), household protein supply (63.5%), and school fees (56.8%). Major sources of information on Newcastle vaccines were through fellow farmers (71.7%) and radio programmes (60.9%). Newcastle disease significantly reduced key productivity metrics and income as egg production: decreased by 2.5 eggs/hen/month, flock survival: declined by 8%, growth rate: dropped by 15g/week, feed conversion efficiency: reduced by 0.8g gain/kg feed, marketable birds: decreased by 4 chickens/month, egg weight: reduced by 0.4g, income: declined by ₦18,000 on average. %). The study concluded that Newcastle disease have negative impact on the livelihood smallholder indigenous farmers. It is recommended that development partners and extension agencies should design and deliver regular poultry health and ND prevention training programs in local languages using simple, practical demonstrations that reflect the farmers’ literacy levels and socio-economic characteristics.